2019 ICSID Annual Report : Excellence in Investment Dispute Resolution - International Centre for Settlement of Investment Disputes (Washington, DC: ICSID, 2019)
ICSID is an international facility available to States and foreign investors for the resolution of investment disputes. Established in 1966 by the Convention on the Settlement of Investment Disputes between States and Nationals of Other States (the ICSID Convention), it is the only global institution dedicated to international investment dispute settlement. Through its specialized rules of procedure, world-class facilities, and expert legal and administrative support, ICSID provides unparalleled dispute resolution services to States and investors. Since the first case was registered with ICSID in 1972, the majority of all known international investment disputes have been administered by ICSID.